The Use of Slang Words of Bruno Mars Songs - Oviana D.Y Libing; I Nengah Sudipa; I Nyoman Aryawibawa (Research and Community Services Institutes of Udayana University, 2023)
This study aims to identify the types of slang words and the meaning of slang words implied in Bruno Mars songs. The researcher divides the data into two parts which are primary data and secondary data. Primary data was taken from the internet in the form of Bruno Mars songs’ lyrics. The previous study and journal were taken as the secondary data to support this research. The methods used in this study is the qualitative descriptive and documentation technique. The main theory that the researcher used is the theory of slang proposed by Eric Partridge (1954). The result of this study shows that there are two types of slang words that contained in Bruno Mars songs lyric. Furthermore the meaning of slang words that implied in Bruno Mars songs lyric is refers to him as a singer.